Indaziflam: Control effectiveness in monocotyledonous and eudicotyledonous weeds as a function of herbicide dose and soil texture - da Silva, Paulo Vinicius (2021)
Background and Objective: The indaziflam herbicide has efficiency in the control of monocotyledons weeds and is recommended for some eudicotyledonous species. However, the efficiency of the control can vary to the detriment of the species, dose and soil texture. Therefore, the objective of the present work was to evaluate the effectiveness of the control of indaziflam herbicide for weeds species Mucuna aterrima, Sorghum halepense, Ipomoea purpurea, Rottboellia exaltata, Urochloa decumbens, Merremia aegyptia, Cenchrus echinatus, Digitaria horizontalis, Panicum maximum, Tridax procumbens, Urochloa plantaginea and Eleusine indica, besides elaborating the calculation of DL80, DL90 and DL95 of the product in two types of soil. Material and Methods: Thus, experiments were carried out in a greenhouse, isolated for each weed species, in a completely randomized experimental design, with four replications and a 10×2 factorial scheme, with ten doses of the herbicide indaziflam (0 D, 1/16 D, 1/8 D, 1/4 D, 1/2 D, D, 2 D, 4 D, 8 D, 16 D, being D = 100 g haG1), applied in pre-emergence and two contrasting soil textures (clayey and sandy). At 7, 14, 21, 28, 35, 42, 49 and 56 days after weed emergence (DAE), visual control assessments were performed and in the last evaluation, the dry mass of the aerial part was performed. Results: The weeds of the Poaceae family showed greater susceptibility to the indaziflam herbicide, on the other hand, the Mucuna aterrima, Ipomoea purpurea and Merremia aegyptia weeds required a higher dose of active ingredient to be controlled efficiently. Conclusion: In general, the current study concluded that a lesser amount of active ingredient was needed in sandy soil than in clayey soils to promote adequate weed control. Therefore, the difference in the susceptibility of the studied plants as function of dose indaziflam, weeds species and soil texture.